CSIG-25. EPIDERMAL GROWTH FACTOR RECEPTOR EXTRACELLULAR DOMAIN MISSENSE MUTATION A289V AS A DRIVER OF GLIOBLASTOMA INVASION AND PROLIFERATION. (5th November 2018) - Binder, Zev; Thorne, Amy; Bakas, Spyridon; Wileyto, E Paul; Akbari, Hamed; Rathore, Saima; Min Ha, Sung; Zhang, Logan; Idbaih, Ahmed; Bagley, Stephen; Morrissette, Jennifer; Nasrallah, MacLean; et al.
Abstract: Epidermal Growth Factor Receptor (EGFR) missense-mutations in glioblastoma (GBM) typically occur within the extracellular domain (ECD) and, to-date, have not shown a clinical impact. These ECD mutations, while not as common as wild-type amplification or EGFRvIII, do represent a distinct patient population in need of investigation. This study investigates the oncogenic effect of the most common EGFR ECD missense-mutations (R108K, A289D/T/V, and G598V) in a retrospective cohort of 260 de novo GBM patients from the University of Pennsylvania. Extrapolation of each individual missense-mutation revealed a significant reduction in patient survival for the EGFR A289D/T/V mutants (p=0.028). This effect was confirmed with a follow-up cohort of 111 patients. The Cancer Imaging Phenomics Toolkit (CaPTk – www.cbica.upenn.edu/captk ) was used to extract 2104 quantitative imaging phenomic (QIP) features, from multiparametric magnetic resonance imaging, across the various tumor sub-regions comprising the enhancing and non-enhancing tumor core, as well as the peritumoral edematous/invaded tissue. Multivariate machine learning techniques integrated these features, revealing radiographic signatures suggestive of increased invasion and proliferation for patients bearing the A289 mutation. The underlying mechanism of EGFR A289V in tumor growth was examined using engineered U87 glioma cells and patient-derived HK281 glioma spheres simulating expression of wild-type-EGFR or EGFR A289V . Corroborating our findings in patients, mice bearing intracranial tumors with EGFR A289V mutations revealed significantly worse survival accompanied by highly invasive tumors. Cells expressing EGFR A289V yielded a highly active EGFR/ERK signaling pathway, resulting in increased expression and functionality of the matrix metalloproteinase MMP1, which can be attenuated by the use of ERK pathway inhibitors. Collectively, the findings of this study highlight a highly invasive and proliferative phenotype associated with the EGFR A289V missense-mutation. Moreover, given the tumor-specific and extracellular nature of the mutation, we postulate that it may be amenable to targeted therapy. Key data presented is from a manuscript with preliminary acceptance to Cancer Cell. *equal contribution